Jaminan Kesejahteraan Istri Dan Anak Perspektif Al-Qur’an - Latif, Adri; Ridha Rosyadi, Muhammad Arief; Meidina, Ahmad Rezy (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2023)
Provision iof ipost-divorce isupport ifor iwives iand ichildren iis ioften iignored iand iabandoned iby iex-husbands. iThere iis ianiassumption ithat icourt idecisions iare ionly ia iproduct iof istate ilaw iso ithat ithey ihave ino iconsequences ifor iGod iis ione iof itheifactors. iThis iunderstanding ineeds ito ibe istraightened iout. iThis ipaper iseeks ito iprovide iawareness ito ithe ipublic, ithat itheiobligation ito iprovide ipost-divorce isupport ifor iwives iand ichildren icannot ibe iabandoned iimmediately iby ihusbandsiwithout iany ireasons ithat ican ibe itreated ias ilegal iillat. iThe iexistence iof ithis ipaper iaims ito iprovide ia idetailed iexplanationiof ithe iguarantee iof ithe iwelfare iof ihis iwife iand ichildren iwhich iis imandated ithrough ithe iword iof iGod.This iresearch iisidescriptive iby iusing ia ijuridical-normative iapproach. iThe iresults iof ithis istudy iare ithat ithere iis ino igap ito ideny ithe ijudge'sidecision iregarding ithe idetermination iof ipost-divorce iprovision. iJudges ias irepresentatives iof iGod ion iearth iand itheiridecisions ican ibe iinterpreted ias iprovisions ifor ithe irealization iof ithe ibenefit iof ithe iummah imust ibe irealized.